Microbial protein estimation in Murrah buffalo calves fed on diets with varying levels of energy and protein - PRUSTY, SONALI; KUNDU, S S; TALUKDAR, PAPORI (The Indian Journal of Animal Sciences, 2017)
A study was conducted to predict the effect of energy and protein levels in diet on rumen microbial protein production in Murrah buffalo calves. Microbial protein was estimated from urinary excretion of purine derivatives. Six diets were formulated to provide 90% (12.30% CP), 100% (13.70% CP), and 110% (15.15% CP) protein level, and 90% (2.20 Mcal ME/kg DM) and 110% (2.42 Mcal ME/kg DM) energy level of ICAR 2013 recommendations for buffalo calves. Thirty calves (body weight; 254±7.4 kg) were divided into 6 groups and fed in 2×3 factorial designs. Dry matter intake was recorded by feeding animals for experimental period of 150 days. At the end of feeding trial, urine samples were collected. Collection, preservation, analysis and calculation of urinary purine derivatives were performed by methods described by IAEA (1997). Allantoin constituted the principal PD in the urine. Allantoin and uric acid ranged from 19.93 to 21.37 mmol/day and 2.32 to 3.49 mmol/day, respectively. Total PD varied from 23.01 to 24.28 mmol/day, whereas PD per kg BW0.75 was within ranges of 362.77 to 384.23 mmol. The microbial N per kg DOMI or digestible OM retention (DOMR) was significantly higher in lower dietary energy group compared to higher ones. There was no significant effect of the energy and protein levels on allantoin, uric acid, creatinine, total purine derivatives and microbial N production per metabolic body weight (kg) in buffaloes. But microbial N production per digestible organic matter intake increased with decreased energy levels, whereas there was no significant effect of protein levels on it. Thus there was efficient conversion of feed N to microbial protein at CP of 12.3% and ME of 2.20 Mcal/kg DM in 250 kg BW Murrah buffaloes.